Transformation of a business management system in the Russian Federation under the conditions of global digitalization - E. S. Yankovskaya (Путеводитель предпринимателя)
The article provides a systematic overview of the main directions of transformation of business management systems in the context of global digitalization. The new approaches to the management of organizations determined by the processes of servicing and software are shown. Disclosed are the relevant business mechanisms for the relationship between economies of scale and the development of digital platforms.